Electroactive and degradable supramolecular microgels. Issue 42 (23rd October 2019) - Li, Helin; Mergel, Olga; Jain, Puja; Li, Xin; Peng, Huan; Rahimi, Khosrow; Singh, Smriti; Plamper, Felix A.; Pich, Andrij
Abstract : In this work, we synthesized electroactive and degradable microgels based on biomacromolecular building blocks, which enable the controlled release of therapeutic drugs. Abstract : In this work, we synthesized electroactive and degradable microgels based on biomacromolecular building blocks, which enable the controlled release of therapeutic drugs. Functional chitosan–poly(hydroquinone) (Ch:PHQ) microgels exhibiting redox-active and pH-sensitive properties were synthesized by an oxidative polymerization in an inverse miniemulsion system. Physically crosslinked microgels were formed by polymerization of hydroquinone in the presence of chitosan through the formation of hydrogen bonds between PHQ and Ch. A series of microgel samples with variable Ch : PHQ ratios were synthesized. These obtained microgels exhibit pH-responsive properties due to the protonation/deprotonation of amino-groups of chitosan in the microgel system. Poly(hydroquinone) is a redox-active polymer exhibiting a two-electron/proton-transfer behavior and conveys this property to the microgels as confirmed by cyclic voltammetry. In addition, the microgels can be switched by electrochemical means: they swell in the oxidized state or shrink in the reduced state. In the presence of urea or lysozyme, the microgels undergo a fast degradation due to the disruption of hydrogen bonds acting as physical crosslinks in the microgel networks or due to the cleavage of glucosidic linkages of the incorporated chitosan scaffold, respectively. Doxorubicin (DOX), an anticancer drug, could be effectively encapsulated into the microgels and released in the presence of an enzyme, indicating that these biodegradable microgels could be used as drug delivery vehicles for tumor cells.